Electronic Properties and Dissociative Photoionization of Thiocyanates : Part II. Valence and Shallow-Core (Sulfur and Chlorine 2p) Regions of Chloromethyl Thiocyanate, CH2ClSCN - Rodríguez Pirani, Lucas (2012)
A combination of photoelectron spectroscopy and synchrotron based photoelectron photoion coincidence (PEPICO) spectra has been applied to investigate the electronic structure and the dissociative ionization of the CH2ClSCN molecule in the valence region. The PES is assigned with the electronic structure calculations at the outer-valence Green’s function and symmetry adapted cluster/configuration interaction (SAC-CI) levels offer an explanation of our experimental results. Upon vacuum ultraviolet irradiation the lowlying radical cation, located at 10.39 eV is formed. The molecular ion is observed in the time-of-flight mass spectra, together with the CH2SCN⁺ and CH2Cl⁺ daughter ions. The total ion yield spectra have been measured in the S 2p and Cl 2p regions and several channels have been determined in dissociative photoionization events for the coreexcited species. Thus, by using time-of-flight mass spectrometry and synchrotron radiation the relative abundances of the ionic fragments and their kinetic energy release values were obtained from both PEPICO and photoelectron photoion photoion coincidence spectra. Possible fragmentation processes are discussed and compared with that found for the related CH3SCN species.